Antihypertensive potential of sweet Ala-Ala dipeptide and its quantitation in dry-cured ham at different processing conditions. (December 2021) - Heres, Alejandro; Yokoyama, Issei; Gallego, Marta; Toldrá, Fidel; Arihara, Keizo; Mora, Leticia
Graphical abstract: Highlights: Quantitation of AA reached 230 µg/g of dry-cured ham after 12-month of ripening. No statistical influence of salt reduction was found on the AA level in dry-cured ham. AA in vitro inhibits ACE-I and is predicted to dock within its S2 site. AA exerts hypotensive effects in orally treated SHR after 4 h and up to 24 h. Abstract: Sweet dipeptide Ala-Ala (AA) could be one of the most abundant dipeptides naturally generated in meat products due to the high occurrence of its sequence all along endogenous proteins, which means it could play a key role in dry-cured ham flavour development and bioactivity. In this study, a mass spectrometry in tandem methodology was optimised to quantitate the dipeptide AA in dry-cured ham manufactured under different processing conditions. Dipeptide values reached 230 µg/g after 12-month of ripening, but statistically insignificant differences were observed with salt reduction. Regarding its antihypertensive activity, an IC50 value of 110.824 µM was determined from the in vitro inhibition of angiotensin-I converting (ACE-I) enzyme, and the oral administration of 1 mg of AA per kg of body weight showed a significant reduction of the systolic blood pressure (SBP) in spontaneous hypertensive rats (SHR). This study elucidates the importance of AA dipeptide and its potential role in cardiovascular health after dry-cured ham consumption.